1998
DOI: 10.1055/s-1998-1872
|View full text |Cite
|
Sign up to set email alerts
|

Model Study of the Hoppe Reaction Between Racemic Titanated Crotyl Carbamate and Enantiopure Aldehyde or γ-Lactol

Abstract: In our strategy for the total synthesis of tylonolide 2, aglycon of tylosin 1, and for the construction of the eastern part C1-C9, we planned to carry out a Hoppe homoaldolisation. In a model study, reaction was performed between racemic titanated crotyl carbamate (±)-3b and optically active aldehydes 6a-c. The expected syn-anti adducts 7a-c were obtained in good isolated yield together with the antianti isomer 8a-c. Interestingly, the γ−lactol 6d was also tested and delivered the syn-anti 7d compound in 70% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 4 publications
(8 reference statements)
0
5
0
1
Order By: Relevance
“…Die 5S,6S,ZKonfiguration von 11 b wurde durch eine Röntgenstruktur-analyse aufgeklärt. [9,17] Zuvor haben wir, [18] wie auch andere Arbeitsgruppen, [19] demonstriert, dass a-Carbamoyloxyallyltitan-Verbindungen unter vollständigem Chiralitätstransfer mit Aldehyden über einen Zimmerman-Traxler-Übergangszustand [11] reagieren. Dadurch lässt sich die S-Konfiguration der Allyltitanverbindung 10 ableiten.…”
Section: Seinunclassified
“…Die 5S,6S,ZKonfiguration von 11 b wurde durch eine Röntgenstruktur-analyse aufgeklärt. [9,17] Zuvor haben wir, [18] wie auch andere Arbeitsgruppen, [19] demonstriert, dass a-Carbamoyloxyallyltitan-Verbindungen unter vollständigem Chiralitätstransfer mit Aldehyden über einen Zimmerman-Traxler-Übergangszustand [11] reagieren. Dadurch lässt sich die S-Konfiguration der Allyltitanverbindung 10 ableiten.…”
Section: Seinunclassified
“…In the Ni 0 -catalyzed ACCRs the sulfoximine group showed an exceptional ability to function as a nucleofuge. Because of a formal analogy between the nickel-ate complex (Z)-3 and the higher order (HO) cuprates (E)-7 and (Z)-7 (Scheme 3), we became interested to see 1) whether HO cuprates of this type can be generated from (Z)-2 and (E)-2, respectively, and organocuprates and 2) if they would undergo a stereoselective copper-based 1,2-MR [6,[11][12][13][14] to give the corresponding lower order (LO) cuprates (Z)-8 and (E)-8, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It had been shown that cuprates (E)-11, which were prepared from the lithiated or stannylated alkenyl carbamates (Z)-10 and LiCu(R 3 ) 2 , readily undergo a 1,2-MR with formation of the alkenyl cuprates (Z)-12, the trapping of which with electrophiles afforded (E)-9. [6,12] This route which can, however, only provide an access to the (E)-configured homoallyl alcohols (E)-9 is hampered by the limited stability of the a-lithioalkenyl carbamates (Z)-10, which suffer an elimination with formation of the corresponding alkynes even at low temperatures. [6,12] In contrast, the lithioalkenyl sulfoximines (Z)-2 and (E)-2 are stable towards elimination up to room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The configuration of 11 b in the solid state could be determined by an X-ray analysis to be 5S,6S,Z. [9,17] Previously we [18] and others [19] demonstrated that chiral a-(carbamoyloxy)allyltitanium compounds react with chiral aldehydes with strict chirality transfer from the Zimmerman-Traxler transition state. Thus we deduce that the titanium intermediate 10 has S configuration, and 10 must be formed from (S)-8 with inversion of configuration.…”
mentioning
confidence: 99%